2018
DOI: 10.18203/issn.2454-2156.intjscirep20184191
|View full text |Cite
|
Sign up to set email alerts
|

Study of good pharmacy practice in community pharmacy of three districts of Kathmandu valley, Nepal

Abstract: <p class="abstract"><strong>Background:</strong> Medicines are an essential component of health-care services. The community pharmacies have great value in terms of providing medicinal services in developing countries. Good Pharmacy Practice (GPP) assesses whether the medicines are safe, effective, available, and accessible and are used correctly. The objective of the study is to assess the good pharmacy practice among community pharmacy of Kathmandu, Bhaktapur and Lalitpur districts.</p&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 7 publications
0
8
1
Order By: Relevance
“…Similarly, previous studies among community pharmacies and PHCs in Nepal also revealed higher non-pharmacy professionals in dispensary roles. 10,21 This can be considered as the reason for low dispensing time, improper labeling, and patient knowledge in medicine. The lack of qualified health personnel was considered in resulting inadequate labeling of medications and insufficient time to counsel patients on the appropriate use of medicine like administration procedures, possible drug-food interactions, and side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous studies among community pharmacies and PHCs in Nepal also revealed higher non-pharmacy professionals in dispensary roles. 10,21 This can be considered as the reason for low dispensing time, improper labeling, and patient knowledge in medicine. The lack of qualified health personnel was considered in resulting inadequate labeling of medications and insufficient time to counsel patients on the appropriate use of medicine like administration procedures, possible drug-food interactions, and side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…More awareness needs to be created of the current GPP guidelines among pharmacists, and special training on GPP adherence may be conducted. Two studies conducted among community pharmacists reported poor compliance with GPP guidelines 26 , 62 . Though the setting is different, this may also have implications for pharmacy practice in hospital pharmacies.…”
Section: Discussionmentioning
confidence: 99%
“…Since many pharmacies in Nepal are still run by unqualified persons 26 , 27 , the status of PC in actual practice is questionable. To enhance the quality and standard of overall pharmaceutical service by pharmacists, the Nepal Pharmacy Council (NPC) developed the National Good Pharmacy guideline draft in 2005.…”
Section: Introductionmentioning
confidence: 99%
“…While research findings confirm the existence of the private drug retail outlets that do not comply with regulatory standards in many low-income countries, there are a lack of reports that evaluates the quality of medicines from these retailers. [11][12][13][14][15][16][17][18] Therefore, the quality amoxicillin 500 mg capsule samples were evaluated using the method mentioned in US Pharmacopeia after assessments of regulatory compliance of the drug retail outlets in Southwestern Ethiopia. In this study, 42 private drug retail outlets of Jimma town were evaluated for regulatory compliance using the Ethiopian regulatory standard checklists.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, widespread regulatory infringement has been reported in private drug retail outlets, especially in developing countries. [11][12][13][14][15][16][17][18] In these retail outlets, personnel requirements, structural design features for the premises, minimum equipment and material requirements, and provisions for good medicine storage and dispensing practices did not fully meet the regulatory standards of those countries. Conversely, while these findings confirm the existence of private drug retail outlets that do not comply with regulatory standards in many low-income countries, there are a lack of reports that evaluate the quality of medicines obtained from these retail outlets.…”
Section: Introductionmentioning
confidence: 99%